Asthma COPD overlap syndrome (ACOS) - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2016)
Asthma and chronic obstructive pulmonary disease (COPD) are the two most prevalent obstructive diseases of the lung. Although asthma and COPD differ in many ways some properties of each disease co-exist in some patients, particularly in patients with advanced age which recently brought up the term

Asthma-COPD Overlap Syndrome (ACOS). In addition to the fact that clinical trials deliberately exclude the patients in this group, the diagnostic criteria of ACOS are not well established. Both of these factors contribute to paucity of evidence based clinical information about ACOS. In this article my aim is to provide brief information about the history, description, clinical properties and treatment of this disease.
Keywords: ACOS; COPD; Asthma; Guideline